Surface and solution behavior of the mixed dialkyl chain cationic and nonionic surfactants. - Penfold, J; Staples, E; Tucker, I; Thomas, R (2004)
The surface and solution behavior of the mixed dialkyl chain cationic and nonionic surfactant mixture of dihexadecyldimethylammonium bromide, DHDAB, and hexaethylene monododecyl ether, C12E6, has been investigated, using primarily the scattering techniques of small-angle neutron scattering and neutron reflectivity. Within the time scale of the measurements, the adsorption of the pure component C12E6 at the air-solution interface shows no time dependence. In contrast, the adsorption of the DHDAB/C12E6 mixture and pure DHDAB has a pronounced time dependence. The characteristic time for adsorption varies with surfactant concentration, composition, and temperature. It is approximately 2-3 h for the DHDAB/C12E6 mixture, dependent upon concentration and composition, and approximately 50 min for DHDAB. At the air-solution interface, the equilibrium composition of the adsorbed layer shows a marked departure from ideal mixing, which is dependent upon both the solution concentration and the concentration of added electrolyte. In contrast, the composition of the aggregates in the bulk solution that are in equilibrium with the surface is close to ideal mixing, as expected for solution concentrations well in excess of the critical micellar concentration. The structure of the mixed adsorbed layer has been measured and compared with the structure of the equivalent pure surfactant monolayer, and no substantial changes in structure or conformation are observed. The extreme departure from ideal mixing in the adsorption behavior of the DHDAB/C12E6 mixture is discussed in the context of the structure of the adsorbed layer, changes in the underlying solution structures, and the failure of regular solution theory to predict such behavior.